Analysis of risk on construction site - Nurul Jannah , Aziz (2012)
Construction industry is one of the largest economy industries that contributed to the development and prosperous of Malaysia. Besides compared with the many other industries, the construôtion industry is subject to more risks due to unique features of construction activities, such as long period, complicated processes, abominable environment, financial intensity and dynamic organization structure. This study are purpose to recognize the risk that always occur on construction site. This study also circumstances the application of the solution to prevent or reduce the risk on construction site. The questionnaire has been prepared and distributed to the site participant either directly or indirectly which is involved in variation level on construction site. Result of the study found that the time management problem is major types of risk in resources management and falling during work at height is a major risk in construction site activities. The result shows that management should well planning the process of a project before start to achieves target reduce risk on construction site.